The Hydrophobicity and the Antibacterial Activity of Polyester Modified With Silver Nanoparticle and Hexadecyltrimethoxysilane - Eli Rohaeti; Anna Rakhmawati (Universitas Jenderal Soedirman, 2017)
The objective of this research were to study hydrophobicity and antibacterial activity of polyester fibers before and after modification by using silver nanoparticles as antibacterial agent and hexadecyltrimethoxysilane (HDTMS) as self cleaning agent. The research was conducted in stages, chemical preparation of silver nanoparticles, deposit of silver nanoparticles on polyester fiber, modification of polyester fiber through the addition HDTMS, and characterization. Modification of polyester fibers with silver nanoparticles and HDTMS was conducted through dipping method, followed by curing. Characterization was conducted by testing the contact angle and antibacterial activity against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218. Silver nanoparticles has been prepared by adding sodium citrate and polyvinylalcohol as stabilizer. The addition of silver nanoparticles decreased hydrophobicity of polyester fibers without and with modification. Modification with HDTMS increased hydrophobicity of polyester fibers. Modification with silver nanoparticles and HDTMS increased antibacterial activity of polyester fabrics. Statistic analysis showed that there were significant differences in the antibacterial activity of polyester fibers against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218